重庆市及三峡库区公路骨架网规划和实施的效益评估 = Economic efficiency analysis of the highway skeleton planning and implementation in Chongqing municipality and three Gorges region - 谭宏 Tan, Hong (2008)
Based on the analysis of the current situation of and future demands for transportation in Chongqing and Three-gorges area, this thesis studies comprehensively the transportation structural scale and its influence on the economic and social development in the region. The important impact of planning and implementation of the highway skeleton on the population and production in the region is thoroughly studied. A long term development strategic highway system planning in early 21th century is proposed for rapid and sustainable economic and social development in Chongqing municipality and Three Gorges area. It will be of great help to maintain Chongqing's regional economic hub status in the western China.